PP.16.38: CARDIOVASCULAR EFFECTS OF SPORTS ACTIVITIES IN HYPERTENSION. (June 2015) - Vriz, O.; Jaroch, J.; Rychard, W.; Loboz-Grudzien, K.; Diussi, C.; Mos, L.; Antonini-Canterin, F.; Palatini, P.
Abstract : Objective: Regular physical activity (PA) has a beneficial effect on the cardiovascular system but the impact of PA on the structural and functional properties of the heart and vessels in hypertension is not completely defined. Design and method: We addressed this issue in 243 normotensive and 172 hypertensive subjects (30% women) with a mean age of 47 ± 16 years. Sports activities were performed by 126 subjects (30%). Heart rate was 67 ± 10 bpm in the sedentary and 57 ± 13 bpm in the active subjects (p < 0.001). Left ventricular (LV) mass index (LVMI) and diastolic function (E/A ratio) were assessed with echo-doppler technique. Wave intensity analysis (W1 and W2) was performed at the level of the common carotid artery with an Aloka alfa 10 ultrasonographic system. Non-invasive one-point measurement of carotid pulse wave velocity (PWV) and augmentation index (AI) was made using a high definition echo-tracking system implemented in the echo-machine. Results: Among the normotensive subjects, age-and-sex-adjusted LVMI was greater in the active than sedentary subjects (mean ± SEM, 164 ± 4 vs 196 ± 6 g/m2), whereas an opposite trend was found among the hypertensives (202 ± 5 vs 187 ± 10 g/m2, respectively) with a highly significant PA-hypertension interaction (p < 0.001). An interactive effect was also found for relative wall thickness (p = 0.009). An E/A improvement was found in both active groups (p < 0.001) with a value that was higher in the active hypertensives (1.77 ± 0.1) than the sedentary normotensives (1.57 ± 0.05). W2, an index of early diastolic performance, was increased in the active compared to the sedentary subjects (p = 0.004), whereas no difference was found for W1. Both PWV (p < 0.001) and AI (p = 0.039) were higher in the hypertensives than the normotensives. PWV was lower in the active than sedentary subjects (p = 0.008). However, AI was increased in the former (p = 0.032). Both PA-related differences disappeared after adjustment for heart rate (P > 0.41). Conclusions: In conclusion: 1) PA has beneficial effects on the heart with opposite structural effects in hypertension and normotension. 2) PA improves arterial distensibility in hypertension as indicated by the lower PWV. The apparent contradictive results obtained from AI measurement seem to be due to the bradycardic effect of PA.